FINANCIAL PERFORMANCE OF MANDIRI BANK AS AN THE BANK RECAPITALIZATION AFTER MERGERS. - Yulianti, Christina Eka (Accounting, 2010)
Since 1997 Indonesia was hit by the economic crisis that caused all the potential to weaken the economy including the financial services sector. The weakening of the financial services sector, particularly banks greatly affect the real sector activities. In addressing the government made it policy to restructure SOE. One way is to merge four state banks into one bank, namely Mandiri Bank, Mandiri Bank hoping to fulfill their function as financial intermediaries that support real sector in Indonesia. Previous research shown that the performance of four state banks namely Bank Exim, Bank BDN, BBD Bank, and Bank Bapindo before the merger is not healthy. This study analyzes the performance of Bank Mandiri past eight years with the ratios ROA, ROE, DER and DTAR. The result of calculation of this ratio is also supported by NPL ratio, CAR, and LDR in 2005. Keyword : Bank, Financial, Merger, Recapitalization